No Recourse to Social Work? Statutory Neglect, Social Exclusion and Undocumented Migrant Families in the UK - Jolly, Andy (2018)
Families in the UK with an irregular migration status are excluded from most mainstream welfare provision through the no recourse to public funds rule, and statutory children’s social work services are one of the few welfare services available to undocumented migrant families. This article draws on semi-structured interviews with undocumented migrant families who are accessing children’s services support to illustrate the sometimes uneasy relationship between child welfare law and immigration control. Outlining the legislative and policy context for social work with undocumented migrant families in the UK, the article argues that the exclusion of migrant families from the welfare state by government policy amounts to a form of statutory neglect which is incompatible with the global social work profession’s commitment to social justice and human rights.